Why do populations float erratically? So many and so few... and its implications for integrated pest management - Hickel, Eduardo Rodrigues; Hickel, Gabriel Rodrigues; Vilela, Evaldo Ferreira; Souza, Og Francisco Fonseca de; Miramontes, Octavio (Revista de Ciências Agroveterinárias, 2007)
Elucidating the intriguing processes that make natural populations oscilate in time has been one of the greatest chalenges for ecologists. This information is crucial for developing mathematical models that allow forecasting the oscilation time and intensity. For agricultural pests, forecasting can result in better timming of control strategies. Several hypotheses have been proposed and some of them have allowed the construction of satisfactory forecasting models, which sometimes lead to paradoxically opposite results. One peculiar characteristic of the models is that, regardless of being based in natural phenomena like density dependence, chaotic, quasi-periodic, and periodic solutions can be achieved with the values of parameter manipulation. More instigating is the scaling behavior in the frequency domain that makes these processes similar to other completely different natural phenomena that belong to the same universal class.